Interactive Learning Multimedia Based on Indonesian Realistic Mathematics Education in Mathematics Subjects - Farhan, Muhamad; I Gde Wawan Sudatha (Jurnal Edutech Undiksha, 2023)
The unavailability of media and learning methods used by teachers in learning mathematics is still simple, resulting in less understanding of students in learning and a decrease in the quality of learning, especially in mathematics subjects. This study aims to create interactive learning multimedia based on Indonesian realistiic mathematics education in grade IV mathematics subjects. This type of research uses development with the ADDIE model. The test subjects consisted of 3 experts and 12 fourth grade students. Data obtained with quantitative and qualitative data. The methods used were questionnaires and tests. Furthermore, the data were analyzed with descriptive qualitative techniques, descriptive quantitative and inferential statistics. Media feasibility is determined from the assessment results of learning content experts (91.66%), learning design experts (92.18%), learning media experts (88.33%), individual test results (87.38%), and small group test results (87.73%). So it is concluded that interactive learning multimedia based on Indonesian realistic mathematics education is feasible to be implemented in learning mathematics grade IV MI. This research has implications for the implementation of realistic and varied learning activities. The implication of this research is the increasing availability of learning tools, namely interactive learning multimedia according to student needs, able to increase student motivation in learning mathematics.